Developing city branding strategy of Ternate in North Moluccas - Indonesia - Mihardja, Eli Jamilah; Widiastuti, Tuti; Agustini, Prima Mulyasari (Penerbit Universiti Kebangsaan Malaysia, 2020)
The city of Ternate has an interesting long history supported by beautiful natural scenery and rich culture. However, these days, Ternate has not yet identified its identity and branding. Storytelling is one of the instruments to form city branding (Keskin et al., 2016). Given the potential of the long history, cultural and natural wealth of Ternate, storytelling can be used as a strategy to form city branding. The research methodology used in this research is a case study. Data was collected through in-depth interviews, observation, and literature study. Fieldwork was carried out in Ternate and surrounding areas in September 2019. Data was analysed using the City’s Core Story (Keskin, Akgun, Zehir & Ayar, 2016). The results show that the city of Ternate has suitable material to develop this storytelling method because of its historical and cultural richness, although in its regional planning this is not a priority. It is interesting to develop the historical plot owned by Ternate in storytelling as a tool for city branding strategy, by compiling a plot as a part of the story. This is appropriate when the City of Ternate stakeholders are conducting a study of the city branding of Ternate. The results of the study could be used as recommendations for policy makers in Ternate regarding storytelling strategies to form city branding. These are also a novelty in developing city branding strategy in Indonesia.